PERLINDUNGAN HUKUM TERHADAP HAK KONSUMEN DALAM INDUSTRI PERUMAHAN MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Supriatiningsih, Eka (DE'RECHTSSTAAT, 2017)
Housing is a basic human need. But for the majority of the Indonesian people, the word "home" became the term that is very expensive, but the house is a building basic, fundamental and also a prerequisite for everyone to survive and live and enjoy life dignified, peaceful, safe and comfortable. Many problems regarding housing draw made this issue to be studied. Identification of research problems are 1) How is the role and perspectives of Law No. 8, 1999 (BFL) for violation of consumer rights in the housing industry?; 2) The extent to which the responsibility of the developer or developer to default or negligence in carrying out obligations, and how the reality faced by consumers?; 3) what legal action can be taken if a dispute arises consumers with businesses?. This study is a descriptive analysis is intended to provide a detailed overview of the rights of consumers in the housing industry, to see the problems that exist in the present and perspective of research that its analysis leads to the future in order to find the right policy to consumer protection housing. From these results it can be concluded that: 1) the implementation of Law No. 8 of 1999 on Consumer Protection (BFL), especially regarding the implementation of consumer rights cannot be realized as a whole, particularly with regard to the behavior for the rights, such as rights advocacy, the right to obtain redress. 2) On the issue of consumer protection, based on the findings directly in the field indicates that Act No. 8, 1999 do not yet play as expected at the time of enactment. 3) Control the government to businesses in the housing industry or developers so far only limited to licensing only, while the interactions or direct relationship between developers and consumers, the government does not intervene. On the advice of the above conclusions are: 1) There needs to be a social movement about empowering consumers so considered important encouragement for socialization activities; 2) Establishment of an independent body specialized dispute resolution field of housing or property in Indonesia is quite urgent, given the weak position of the consumer; 3) For a more integrative and comprehensive reach the target of legal protection to consumers, Act No. 8 of 1999 on Consumer Protection in the implementation must be accompanied by implementing regulations.